O DIRETOR ESCOLAR E A IDÉIA DE DEMOCRACIA: UM OLHAR A PARTIR DA FORMAÇÃO - Lima, Reinaldo Inácio de (2006)
This assignment presents a reflection and a discussion about democracy models present in the managers and in their educational practices. This reading is done from the formation process that include all the trajectory of involved people to search the ways of appropriation of democracy ideals present in each one and in their formation stages to life and profession. The theoretical support basis on to hear/to tell , that means, in the oral narrative of stories life from each one envolved. Childhood, youth and maturity permeate the search of answers to the agents references that each one have. I talked to the interviewed memories to discover the idea that each one have about democratic management. I looked to their own personal thoughts and I discovered a complex universe more different than I found in bibliographies about this subject. I discovered that people build their conceptions during their lifes and link with them through formal situations, as the profession. This assignment is structured in three chapters and annexes.